Multidrug-Resistant Methicillin-Resistant Coagulase-Negative Staphylococci and Staphylococcus aureus in Cattle and Goats from the East Coast of Peninsular Malaysia - Mohamad, N. M.; Zakaria, P. N. M.; Suhaili, Z.; Abu Bakar, S. A.; Aklilu, E. (Faculty of Animal Science, IPB University, 2025)
This study investigates the prevalence and antimicrobial resistance profiles of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant coagulase-negative staphylococci (MRCoNS) in livestock from Kelantan, Terengganu, and Pahang, Malaysia. Nasopharyngeal swabs from 290 goats and 106 cattle were processed using an improved transport and enrichment method. Staphylococci were identified via PCR targeting the nucA and mecA genes, with antimicrobial susceptibility determined according to CLSI and EUCAST guidelines. Among 396 isolates, 55 (13.9%) were identified as S. aureus, including one MRSA isolate (0.25%), and methicillin resistance was detected in 31 CoNS isolates (7.8%), predominantly from goats. Fourteen of the MRCoNS isolates exhibited multidrug resistance to 3 to 7 antibiotic classes, with 47.2% of CoNS isolates being resistant to fusidic acid, raising concerns about zoonotic transmission and public health risks. The prevalence of staphylococcal colonization and methicillin resistance was higher in goats than in cattle, suggesting that environmental exposures, management practices, and antibiotic use contribute to the resistance patterns. The findings highlight the urgent need for enhanced biosecurity measures, prudent antibiotic use, and expanded surveillance to address antimicrobial resistance in livestock. A One Health approach that integrates human, animal, and environmental health is essential to mitigating the spread of resistance. This study provides baseline data to guide future research, interventions, and policies in reducing public health risks associated with MDR staphylococci in livestock.